Effect of simulation-based training on the accuracy of fetal head position determination in labor. (November 2019) - Barros, Joana G; Gomes-da-Costa, Ana; Afonso, Maria; Carita, Ana I.; Ayres-de-Campos, Diogo; Graça, Luís M.; Clode, Nuno
Abstract: Objectives: The objective of this study was to evaluate the effect of simulation-based training on the accuracy of fetal head position determination by junior residents during the second stage of labour. Study Design: This prospective study was conducted in a tertiary care university hospital. During an initial period of 12 weeks, 13 junior residents were asked to routinely evaluate fetal head position by digital examination during the second stage of labour, in women with term singletons in cephalic presentation. Digital examination was followed immediately by transabdominal ultrasound to confirm fetal head position, performed by an experienced physician. Following this initial period, all participants attended a workshop where simulation-based training of fetal head position determination was provided. A second 12-week period was subsequently completed, with similar characteristics to the initial one. The accuracy of clinical evaluations was assessed by the percentage of exact evaluations, the percentage of correct evaluations within a 45° error margin, and by Cohen's kappa coefficient of agreement. Results: A total of 83 observations were performed in the initial period of the study and 74 observations were performed in the second period. The accuracy of fetal head position determination during the first period of the study was 59.0% (95% CI 47.7–69.7), k = 0.517 (95%CI 0.391 - 0.635), corresponding to a moderate agreement. Considering a 45° margin of error, accuracy was 71.1% (95% CI 60.1–80.5), k = 0.656 (95% CI 0.538 – 0.763), corresponding to substantial agreement. Following simulation-based training, the accuracy of fetal head position determination was 70.3% (95% CI 58.5–80.3), k = 0.651 (95% CI 0.526 - 0.785), corresponding to a substantial agreement. Considering a 45° margin of error, accuracy was 78.4% (95% CI 67.3–87.1), k = 0.745 (95% CI 0.631 – 0.854), corresponding to a substantial agreement. Conclusions: Although a trend towards increased accuracy in fetal head position determination was observed after simulation-based training, the difference was not statistically significant. Further studies are needed to clarify the role of simulation-based training for fetal head position determination during residency.